The Development of Activity Literacy Teaching Material Based on Multimodal of Literacy for the grade 4th at SDS Amir Hamzah - Isma Damayanti; Mutsyuhito Solin; Evi Eviyanti (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to: (1) Describe the development of multimodal literacy-based literacy teaching materials at SDS Amir Hamzah. (2) Testing the feasibility of teaching materials for literacy activities based on multimodal literacy at SDS Amir Hamzah. (3) Testing the effectiveness of teaching materials for literacy activities based on multimodal literacy at SDS Amir Hamzah. This research is a development research using the ADDIE development model, namely: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were the fourth grade students of SDS Amir Hamzah in the 2019/2020 academic year consisted of 21 students. The instruments used are questionnaires of expert validity, student and teacher responses, and student performance rubrics using literacy activity teaching materials.  The results of this study indicate that (1) the process of developing teaching materials for literacy activities based on multimodal literacy includes five steps, namely: analysis, design, development, implementation, and evaluation. (2) The literacy activity teaching materials of multimodal literacy-based are feasible to use with an average percentage of 88.47% and very feasible criteria. (3) The effective multimodal literacy-based literacy activity teaching materials are used with a gaincore value of 0.575.